Correction to: Fast and accurate pseudoinverse with sparse matrix reordering and incremental approach (Machine Learning, (2020), 109, 12, (2333-2347), 10.1007/s10994-020-05920-5) - Jung, Jinhong; Sael, Lee (Machine Learning, 2021)
The following acknowledgments were inadvertently left out of the published article.